‘A steadying hand’: Ascribing speech acts to users of predictive speech assistive technologies - Rainey, S (Thomson Reuters, 2018)
Neuroprosthetic speech technologies are in development for patients suffering profound paralysis, such as can result from amyotrophic lateral sclerosis (ALS). These patients would be unable to speak without intervention, but with neurotechnology can be offered the chance to communicate. The nature of the technology introduces a neuroprosthesis that mediates neural activity to generate synthesised speech. How word prediction coheres with speaker intentions requires scrutiny. Some future forms of prostheses, using statistical language models to predict word patterns, could be thought of as participating with communicative intent – not merely channelling it. Concepts relating to vicarious liability, may serve to clarify these issues. This paper is about showing how technology might interact with speaker intent in cases of delegated action, and how it should be seen as participating in the implementation of user ‘instructions’.